Developing online educational modules on the ethical, legal and social issues related to biobanking – a resource for clinicians, researchers and research ethics committees in South Africa - Singh, Shenuka (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.